Unmarriages: Women, Men, and Sexual Unions in the Middle Ages - Karras, Ruth Mazo (The Middle Ages series, 2012)
The Middle Ages are often viewed as a repository of tradition, yet what we think of as traditional marriage was far from the only available alternative to the single state in medieval Europe. Many people lived together in long-term, quasimarital heterosexual relationships, unable to marry if one was in holy orders or if the partners were of different religions. Social norms militated against the marriage of master to slave or between individuals of very different classes, or when the couple was so poor that they could not establish an independent household. Such unions, where the protections that medieval law furnished to wives (and their children) were absent, were fraught with danger for women in particular, but they also provided a degree of flexibility and demonstrate the adaptability of social customs in the face of slowly changing religious doctrine.Unmarriagesdraws on a wide range of sources from across Europe and the entire medieval millennium in order to investigate structures and relations that medieval authors and record keepers did not address directly, either in order to minimize them or because they were so common as not to be worth mentioning. Author Ruth Mazo Karras pays particular attention to the ways women and men experienced forms of opposite-sex union differently and to the implications for power relations between the genders. She treats legal and theological discussions that applied to all of Europe and presents a vivid series of case studies of how unions operated in specific circumstances to illustrate concretely what we can conclude, how far we can speculate, and what we can never know.